The symptom experience of people living with HIV and AIDS in the Eastern Cape, South Africa - Phaswana-Mafuya Nancy; Peltzer Karl (BMC, 2008)
Abstract Background Symptom management for persons living with HIV (PLHIV) or AIDS is an important part of care management. Limited information about symptom prevalence exists about HIV infected persons in South Africa, in particular in the context of antiretroviral treatment (ART). The aim of this study was to assess HIV symptoms and demographic, social and disease variables of people living with HIV in South Africa. Methods In 2007 607 PLHIV, sampled by all districts in the Eastern Cape Province and recruited through convenience sampling, were interviewed by PLHIV at health facilities, key informants in the community and support groups. Results Two-thirds of the PLHIV (66%) classified themselves with being given an AIDS (advanced stage of HIV) diagnosis, 48% were currently on ART, 35% were currently on a disability grant for HIV/AIDS and for 13% the disability grant had been stopped. Participants reported that on the day of the interview, they were experiencing an average of 26.1 symptoms out of a possible 64. In a regression model with demographic and social variables, higher HIV symptom levels were associated with lower educational levels, higher age, urban residence and not on a disability grant, lack of enough food and having a health insurance, and in a regression model with demographic, social and disease variables only being on ART, lack of enough food and having a health insurance were associated with HIV symptoms. Conclusion Symptom assessment provides information that may be valuable in evaluating AIDS treatment regimens and defining strategies to improve quality of life. Because of the high levels of symptoms reported, the results imply an urgent need for effective health care, home- and community-based as well as self-care symptom management to help patients and their families manage and control AIDS symptoms.